Application of a ventilator associated pneumonia prevention guideline and outcomes: a quasi-experimental study - Sousa, Ana Sabrina (2018)
Objective: Ventilator associated pneumonia is the most frequent health-care-associated infection in Intensive Care Units, causing increased antibiotic consumption and resistance, length of stay, plus multiple health and economic costs. The aim of the study was to assess whether a customised guideline implementation would improve ventilator-associated pneumonia incidence and associated intensive care outcomes. Design: This was a quasi-experimental, before-after study consisting of pre-intervention, intervention and post-intervention periods. Setting: Three intensive care units at a well-known Portuguese hospital centre. Intervention: A set of eight recommendations was implemented after a guideline adaptation process. Patients: Adult patients admitted to the intensive care units over the study periods, aged 18 years or older and under invasive ventilation through an endotracheal tube or tracheostomy cannula. Measurements and main results: Data related to patient characterisation, guideline compliance and health outcomes were analysed. From a population of 1970 patients, a study sample of 828 was studied. Compliance with the recommendations was high. We identified a significant reduction in the incidence of ventilator-associated pneumonia in two of the units (p = 0.020 and p = 0.001) and a reduction in duration of invasive ventilation, intensive care unit length of stay and mortality in all the three units. We found associations between some recommendations and the implementation of the set of recommendations and intensive care unit length of stay, duration of invasive ventilation and mortality. Conclusion: The implementation of an evidence-based, locally customised guideline may improve ventilator associated pneumonia incidence and several outcomes.